Using means-end chain analysis to reveal consumers' motivation for buying local foods: An exploratory study - Elton Li; Johan Bruwer; Poppy Arsil (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
This article utilizes and discusses specific aspects of Means-End Chain (MEC) analysis for understanding of the motives of Indonesian consumers who are involved in purchasing local foods. The MEC theory is used as a measure of attributes, consequences, and values of locally produced products involving specific aspects of this theory namely laddering methods of administration, content analysis procedure, constructing and interpreting Hierarchy Value Map (HVM). The results of the study indicate that MEC approach is a powerful method to reveal consumer motivation of local foods when associated with the various cultural groupings identified by the study particular between Javanese and Non-Javanese consumers. This study offers a practical implication and source of knowledge for other future studies and policies in term of (a) a new approach for understanding the motives behind purchasing local foods for Indonesia consumers, and (b) developing new categories of attributes, consequences and values of local foods.